Low Usage of Modern Contraceptives Among Women of Reproductive Age in Tanzania: Analysis Beyond Availability and Awareness Factors - haule, kelvin; Maning, Magreth; Kabigi, Bupe (Tanzania Journal for Population studies and Development, 2024)
Most studies on contraceptives have linked low use with awareness and problems of availability. However, these studies have not considered low or discontinuation of use of contraceptives to be a positive phenomenon where women exercise their reproductive rights or autonomy. Hence, this article has adopted a Marxist-Feminist theory of contraceptives to examine the association between socio-demographic factors and low usage of contraceptives among women of reproductive age. It also evaluates the influence of the availability and awareness on the use or non-use of contraceptives among such a group of women. The article is based on a cross- sectional case study conducted in Kigoma Rural District, Tanzania. The data were collected through questionnaires modified from TDHS, interviews with nurses, and an in-charge of a health facility. Secondary data were collected from TDHS (2016, 2022), Tanzania Service Delivery Point report, Stock Inventory Charts and Our World data sets. Quantitative analysis was performed through STATA 14, and secondary data was processed through content analysis. The study found that though the majority of the reproductive age are aware of contraceptives, most (80%) have not used them. We do not treat this as a problem, but an exercise of reproductive rights and autonomy by women. In addition, there is no significant evidence to prove any influence of socio-demographic factors on low use of contraceptives. Low use and discontinuation of contraceptives are associated with the need for more children by women, and the side effects of contraceptives. Therefore, we conclude that women should be left to decide when and how to use contraceptives: they should not be forced through direct or indirect health services.